Culture and art of immigrants in the Atlantic in the nineteenth and twentieth centuries - Polifroni Lobo, Giovanni; Rocha Alvarez, Delma (Cambridge Scholars Publisher, 2019)
This book presents research on immigrants in South America and Caribbean Colombia and their relationship with the birth and development of the city of Barranquilla. As such, it explores elements that make evident customs and cultural beliefs that have influenced behavior in these regions. It discusses how these practices are reflected in the characteristics of housing, art, and cultural exhibitions, among others.Most societies in these areas have flourished in an uneven and often unequal manner. However, this book will serve to reconcile such cultural groups and create bonds of shared responsi.